Beejal is solving the equation y/7 − 3 = 39

.
As a first step, he starts by adding
what to both sides of the equation, and then continues by multiplying by what
on each side.

1 answer

To solve the equation \( \frac{y}{7} - 3 = 39 \), Beejal can follow these steps:

  1. First Step: Add 3 to both sides of the equation. \[ \frac{y}{7} - 3 + 3 = 39 + 3 \] This simplifies to: \[ \frac{y}{7} = 42 \]

  2. Second Step: Multiply both sides by 7. \[ 7 \cdot \frac{y}{7} = 42 \cdot 7 \] This simplifies to: \[ y = 294 \]

So, Beejal should add 3 to both sides of the equation first, and then multiply both sides by 7.